Immune checkpoint inhibitor-related acquired amegakaryocytosis thrombocytopenia: a case report and literature review - Rivet, Valérian; Sibaud, Vincent; Dion, Jérémie; Volosov, Thibaut; Biteau, Mélanie; Pastissier, Andréa; Delavigne, Karen; Cougoul, Pierre; Rauzy, Odile; Comont, Thibault (Frontiers in Oncology, 2024)
Introduction Immune checkpoint inhibitors (ICIs) are used in several advanced malignancies and may cause various immune-related adverse events (irAEs). Among them, hematological irAEs are less described. Acquired amegakaryocytic thrombocytopenia (AAT) is a rare immune hematologic disorder characterized by severe thrombocytopenia and complete absence of megakaryocytes in bone marrow. Case presentation Herein, we present the case of a patient in their 40s with metastatic melanoma who developed an AAT after 12 cycles of nivolumab (anti-PD1). His platelet count decreased by ≤5 × 109/l without other cytopenia. Bone marrow biopsy showed normal cellularity with a complete absence of megakaryocyte and T-CD8+ lymphocyte infiltration. Given the failure of systemic steroids, eltrombopag was started, an oral thrombopoietin receptor agonist (TPO-RA), and his platelet count subsequently increased with complete response. Discussion Four other cases are described on literature with the same features than non-ICI-related AAT. All cases occurred after anti-PD/PD-L1 treatment with a median onset of 5 weeks. The presentation of our case is quite different with delayed cytopenia. Both ciclosporin and TPO-RA seem to be efficient therapies. Conclusion TPO-RA could be preferred in oncologic patients, but safety data are still missing to define clear guidelines for immune-related AAT management.